Disentangling the factors of contrasting silver and copper accumulation in sporocarps of the ectomycorrhizal fungus Amanita strobiliformis from two sites - Borovička, Jan; Konvalinková, Tereza; Žigová, Anna; Ďurišová, Jana; Gryndler, Milan; Hršelová, Hana; Kameník, Jan; Leonhardt, Tereza; Sácký, Jan (The Science of the total environment, 2019)
Amanita strobiliformis (European Pine Cone Lepidella) is an ectomycorrhizal fungus of the Amanitaceae family known to hyperaccumulate Ag in the sporocarps. Two populations (ecotypes) of A. strobiliformis collected from two urban forest plantations in Prague, Czech Republic, were investigated. The concentrations of Ag, Cu, Cd, and Zn were determined in the mushrooms. The metal mobility and fractionation in the soils was investigated by single extractions and sequential extraction. The soil distribution of A. strobiliformis mycelium was assessed by quantitative polymerase chain reaction (qPCR). The metal uptake from the soil into the mushroom sporocarps was traced by Pb isotopic fingerprinting. The findings suggested that A. strobiliformis (i) accumulates primarily Ag from the topsoil layer (circa 12cm deep) and (ii) accumulates Ag associated with the "reducible soil fraction". The concentrations of all metals, particularly Ag and Cu, were significantly higher in the A. strobiliformis sporocarps from one of the investigated sites (Klíčov). The elevated concentrations of Ag in the sporocarps from Klíčov can possibly be attributed to the higher Ag content in the topsoil layer found at this site. However, the simultaneously elevated concentrations of Cu in A. strobiliformis from Klíčov cannot be explained by the differences in the geochemical background and should be attributed to biological factors.
Keywords: Amanita; Environmental Monitoring; Soil Pollutants; měď; látky znečišťující půdu; Hyperaccumulation; qPCR; monitorování životního prostředí; Soil mycelium quantification; BCR sequential extraction; mykorhiza; stříbro; Mycorrhizae; Silver; (206)Pb/(207)Pb ratio; Copper; Lead isotopes